Cold atmospheric plasma drives USP49/HDAC3 axis mediated ferroptosis as a novel therapeutic strategy in endometrial cancer via reinforcing lactylation dependent p53 expression - Jinlin Liu; Yang Li; Ruonan Ma; Youming Chen; Jinyang Wang; Lindong Zhang; Baojin Wang; Zidi Zhang; Lili Huang; Hongyan Zhang; Junhu Wan; Hongyang Liu (Journal of Translational Medicine)
Abstract Background Endometrial cancer ranks among the most common gynecological cancers, with increasing rates of incidence and death. Cold atmospheric plasma (CAP) has become a promising novel therapeutic approach for cancer treatment. Nevertheless, the specific impact of CAP on endometrial cancer remains inadequately characterized. Objectives This study aimed to investigate the effect of CAP on the progression of endometrial cancer and reveal its specific regulatory mechanisms. Methods Colony formation, EdU, wound-healing, and transwell assay were used to detect the effect of CAP on endometrial cancer progression. Proteomics is employed to identify potential targets and signaling pathways through which CAP impacts endometrial cancer cells. MDA, lipid ROS, and JC-1 MMP assays were used to detect ferroptosis. Immunoprecipitation-mass spectrometry, co-immunoprecipitation, immunofluorescence co-localization, and molecular docking were used to analyze USP49 and HDAC3 interactions. The tumor xenografts model determined that CAP inhibits endometrial cancer growth in vivo. Results This study observed a significant inhibitory effect of CAP on the proliferation and migration of endometrial cancer cells and reported for the first time that CAP induces ferroptosis in endometrial cancer cells. Mechanistically, CAP activated the transcription of p53 by modulating HDAC3 mediated the histone H3K18 lactylation, resulting in upregulation of p53 driving cell ferroptosis. The interaction between USP49 and HDAC3 was validated through mass spectrometry and co-immunoprecipitation experiments. The regulation of HDAC3 by CAP is contingent upon USP49, wherein the down-regulation of USP49 augments the ubiquitination of HDAC3, consequently diminishing its protein stability. Furthermore, animal models with transplanted tumors corroborated the inhibitory impact of CAP on endometrial cancer in vivo. Conclusions Our findings illustrate the suppressive effect of CAP treatment on endometrial cancer and uncover a novel regulatory mechanism mediated by CAP. Specifically, CAP modulates the ferroptosis pathway through the HDAC3/H3K18la/p53 axis, presenting a novel therapeutic approach for endometrial cancer treatment.